Diplomasi Maritim Indonesia dalam Indian Ocean Rim Association (IORA): Peluang dan Tantangan - Dion Maulana Prasetya; Heavy Nala Estriani (Insignia: Journal of International Relations, 2018)
This article analyzed the opportunities and challenges of Indonesia maritime diplomacy in the context of the Indian Ocean Rim Association (IORA). As part of the effort to realize the policy of global maritime fulcrum, Indonesia utilizes maritime diplomacy to look for the close cooperation and agreements with IORA member countries. Up to date, Indonesian foreign policy, specifically in the maritime field is tending to be more dominant to the Pacific Ocean rather than the Indian Ocean. Thus, this paper will explain how Indonesia implements its maritime diplomacy within IORA, and what the opportunities and challenges faced by Indonesia inside the association. Using the method of literature study, this descriptive paper uses the concept of maritime diplomacy and global maritime fulcrum in order to explain the study. This paper argues that IORA’s strategic policy in maritime security and economic policies, links with Indonesia policy in global maritime fulcrum. Thus, Indonesia uses maritime diplomacy to take the advantages and opportunities to enhance maritime connectivity and cooperation with IORA members. Nevertheless, several issues challenge Indonesia like the increasing of great power states maritime influence such as India and China in the Indian Ocean, as well as challenges in integrating IORA member states.